(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the administrative-territorial reforms and demographic changes in the city of Samarkand following Uzbekistan’s independence. During this period, the city’s administrative structure was reshaped, new districts were established, and infrastructure was improved. Additionally, urbanization processes, population density increase, demographic growth rates, migration trends, and economic development-related transformations are discussed. The study provides an overview of Samarkand’s current state and future prospects based on official statistical data and demographic analysis methods.